Socio-Legal Study of Pemena Recognition and Civil Rights - Sembiring, Adventi Ferawati; Ani Purwanti; Sukirno (Jurnal Cakrawala Hukum, 2026)
This study examines the recognition of the local Pemena religion and the fulfilment of the civil rights of its adherents following Constitutional Court Decision No. 97/PUU-XIV/2016. Normatively, this decision marks a significant shift in Indonesian legal policy by recognising adherents of local beliefs as equal legal subjects within the civil registry system. However, in practice, the implementation of this policy still faces various obstacles. This study aims to analyse the form of recognition granted to Pemena and to identify the factors causing the sub-optimal fulfilment of the civil rights of its adherents in Karo Regency, North Sumatra. The research employs a socio-legal approach, combining normative legal analysis with empirical data obtained through interviews with Pemena adherents and relevant officials. The findings indicate that recognition of Pemena remains largely formal and has not yet been fully realised in practice. Pemena adherents continue to face discrimination, both in the form of social stigma and administrative barriers to obtaining civil registration documents. The gap between legal norms and implementation, administrative requirements that are not contextually appropriate, and a lack of understanding among officials are the main factors hindering the effectiveness of this recognition. Thus, although the Constitutional Court’s ruling has opened the door to more inclusive recognition, recognition of the local Pemena faith has not yet reached a substantive stage. More comprehensive efforts are required through administrative policy reform, capacity building for officials, and the strengthening of social awareness to realise fair and non-discriminatory protection of civil rights for adherents of the faith. This study confirms that legal recognition without structural and social transformation tends to result in symbolic recognition, thereby enriching socio-legal studies regarding the protection of religious minority groups.